O niektórych metodologicznych niedostatkach prac z dydaktyki literatury = On methodological anachronisms in works on didactics of literature - Jazownik, Leszek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is devoted to the problems of antipositivistic turning point in the didactics of literature. Its aim is to reconstruct certain views, which seem to prevail nowadays, on the methodological status of this branch of didactics. Representing traditional empirism and naturalism, these views are subject to critical analysis in the present paper.
Keywords: dydaktyka literatury; metodologia